2016
DOI: 10.1002/2015gb005254
|View full text |Cite
|
Sign up to set email alerts
|

Saharan versus local influence on atmospheric aerosol deposition in the southern Iberian Peninsula: Significance for N and P inputs

Abstract: A novel methodology was used to evaluate the contribution of Saharan dust to the atmospheric deposition of particulate material (PM), total phosphorus (TP), and total nitrogen (TN) in the southeastern Iberian Peninsula. Dry and wet aerosol depositions were measured weekly during two 1 year periods at one site and simultaneously during spring-summer of the same years at two other sites (intersite distance of 40 km). Statistical relationships among depositions at the different sites permitted differentiation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…Synchrony in atmospheric deposition among distant sites is used as a signature of meteorological forcing and longrange dispersal [10,24]. Indeed, total deposition rates (i.e., sedimentation in dry collectors plus atmospheric washout in wet collectors) of viruses at OSN and VSN were synchronous (i.e., positively correlated) (r = 0.95, p = 0.000, n = 12) in 2008 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Synchrony in atmospheric deposition among distant sites is used as a signature of meteorological forcing and longrange dispersal [10,24]. Indeed, total deposition rates (i.e., sedimentation in dry collectors plus atmospheric washout in wet collectors) of viruses at OSN and VSN were synchronous (i.e., positively correlated) (r = 0.95, p = 0.000, n = 12) in 2008 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The collectors were installed in 2008 to determine the synchrony (temporal coherence) between sites. Synchrony verifies long-range transport of material vs. local sources of aerosols [10,24]. Dry and wet-deposition buckets were collected every 14 days during 2007 (only at the OSN site), and every 7 days during 2008 (at both sites).…”
Section: Atmospheric Deposition Sampling and Organic Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our simulations, the whole trend of this proxy shows moderate correlations with the NAO index (Supplementary Table S6 ). However, this correlation declines during the last ∼300 years, pointing to a change in aeolian input features likely caused by either recent major variations in Saharan dust composition 23 , 51 , a higher local dust contribution 52 , or some combination.…”
Section: Discussionmentioning
confidence: 97%
“…They represented more than half of the total PM reaching the study area, even though they only accounted for 16% of the events. On the Iberian peninsula, African intrusions usually occur in spring-summer (Castillo et al, 2017), but, as observed here, sporadic intrusions may occur throughout the year, leading to disproportionate outbursts of PM on specific days with significant inputs of minerals such as phyllosilicates, quartz, or calcite (Lequy et al, 2018) and nutrients, particularly phosphorous, which in some ecosystems could be a limiting factor (Morales-Baquero & Pérez-Martínez, 2016). Total PM inputs increased with rainfall due to enhanced wet deposition and the redistribution of previously dry-deposited particulate material (Grantz et al, 2003).…”
Section: Spatiotemporal Variations Of Pm Fluxesmentioning
confidence: 52%